Sedentary Patterns, Physical Activity, and Cardiorespiratory Fitness in Association to Glycemic Control in Type 2 Diabetes Patients - Sardinha, Luís B.; Magalhães, João P.; Santos, Diana A.; Júdice, Pedro B. (Frontiers in Physiology, 2017)
Background: Sedentary behavior has been considered an independent risk factor for type-2 diabetes (T2D), with a negative impact on several physiological outcomes, whereas breaks in sedentary time (BST) have been proposed as a viable solution to mitigate some of these effects. However, little is known about the independent associations of sedentary pursuits, physical activity, and cardiorespiratory fitness (CRF) variables with glycemic control. We investigated the independent associations of total sedentary time, BST, moderate-to-vigorous physical activity (MVPA), and CRF with glycemic outcomes in patients with T2D. Methods: Total sedentary time, BST, and MVPA were assessed in 66 participants (29 women) with T2D, using accelerometry. Glucose and insulin were measured during a mixed meal tolerance test, with the respective calculations of HOMA-IR and Matsuda index. Glycated hemoglobin (HbA1c) was also analyzed. CRF was measured in a maximal treadmill test with breath-by-breath gases analysis. Multiple regressions were used for data analysis. Results: Regardless of CRF, total sedentary time was positively associated with HbA1c (β = 0.25, p = 0.044). Adjusting for MVPA, total sedentary time was related to fasting glucose (β = 0.32, p = 0.037). No associations between total sedentary time and the remaining glycemic outcomes, after adjusting for MVPA. BST had favorable associations with HOMA-IR (β = −0.28, p = 0.047) and fasting glucose (β = −0.25, p = 0.046), when adjusted for MVPA, and with HOMA-IR (β = −0.25, p = 0.036), Matsuda index (β = 0.26, p = 0.036), and fasting glucose (β = −0.22, p = 0.038), following adjustment for CRF. When adjusting for total sedentary time, only CRF yielded favorable associations with HOMA-IR (β = −0.29, p = 0.039), fasting glucose (β = −0.32, p = 0.012), and glucose at 120-min (β = −0.26, p = 0.035), and no associations were found for MVPA with none of the metabolic outcomes. Conclusion: The results from this study suggest that sedentary time and patterns are relevant for the glycemic control in patients with T2D. Still, MVPA and CRF counteracted most of the associations for total sedentary time but not for the BST. MVPA was not associated with metabolic outcomes, and CRF lost some of the associations with glycemic indicators when adjusted for total sedentary time. Future interventions aiming to control/improve T2D must consider reducing and breaking up sedentary time as a viable strategy to improve glycemic control.